A modular visuo-haptic mixed reality (VHMR) aided prototype technique for in-vehicle human-machine interaction (HMI) evaluations. (2nd December 2022) - Song, Dongjin; Yuan, Wenyu; Chao, M. A.; Han, Ting
Abstract : Virtual Prototyping is a robust method to greatly reduce the labour cost and time required of the vehicle prototype. Still, the absence of the haptic sensory channel degrades the immersive experience evaluation, especially in terms of in-vehicle human-machine interaction (HMI). Hence, this study proposed a modular visuo-haptic mixed reality (VHMR) aided prototype technique suitable for in-vehicle HMI evaluations, which positions itself between pure VR technology and physical object assessment. Technology acceptance model (TAM) was also introduced to empirically investigate the perceived usefulness, ease of use, presence, risk, as well as the behavioural intention of the prototype technique separately. Results revealed that the modular visuo-physical object prototype technique has certain advantages in terms of positioning, usability and user acceptance among the VHMR solutions, and could be adopted as a low-fidelity prototype to build common ground in the R&D team and get quick feedback from users for the agile in-vehicle HMI development.